Impact of Correlation on Risky Portfolio Choice, Diversification, and Performance - Kantarelis, Demetri (Advances in Social Sciences Research Journal, 2025)
Using Modern Portfolio Theory, applied on risky (stock) portfolios with real price data, it is shown that lower average portfolio correlation enables the investor to improve diversification and, consequently, experience lower portfolio risk as well as reach higher wealth indifference curves. Based on low and high correlation risky investments, results are calculated for Equally Weighted, Minimum Risk, Maximum Expected Return, and Maximum Sharpe Ratio portfolios. Long position performance is measured in terms of Expected Portfolio Return, Portfolio Standard Deviation, and Sharpe Ratio and, with the help of Monte Carlo simulation, it is shown that low correlation portfolios outperform high correlation portfolios. It is concluded that although low portfolio correlation is, undoubtedly, of paramount importance for diversification and portfolio choice, it is not a panacea: the investor must recognize that she needs both lower correlation and higher expected returns, must take into consideration the fact that the degree of correlation changes over time, and be aware of the fact that sometimes it may be beneficial to include in the portfolio positively correlated assets.